Nomenclatural issues in the Psammodromus hispanicus (Squamata: Lacertidae) species group - Crochet, Pierre-André (Zootaxa, 2015)
The Psammodromus hispanicus species group has been recently shown to include three lineages that differ in morphology (San-Jose et al. 2012), have largely parapatric range but exhibit little evidence of historical gene flow (Fitze et al. 2011), leading to the recognition of these three lineages as distinct species (Fitze et al. 2012). The eastern species can be unambiguously associated with the nomen Lacerta edwarsiana Dugès 1829, as the detailed information in Dugès (1829) leaves no doubt that he describes as Lacerta edwarsiana the local member of the P. hispanicus complex, and the type locality is the “bas Languedoc”, an area of France equivalent to the lowland parts of the current Languedoc region where the only member of the complex is the eastern lineage. The types of Psammodromus edwarsianus have not been traced as far as I am aware, but given the lack of uncertainty regarding allocation of this nomen to the eastern lineage of the P. hispanicus complex this has no nomenclatural consequence. Two nomenclatural issues remain in this species group however: the aim of this note is to solve them.